Virtual Voice Assistant using Python - Agarwal, Ayush; Mishra, Abhineet; Tiwari, Saransh; Singh, Rajan (Journal of Advanced Research in Information Technology, Systems and Management, 2022)
In recent years, Artificial has shown enormous growth and future potential. One of the specific areas where that potential is growing each year is natural language processing (NLP). With the help of artificial intelligence, voice assistants can communicate with users in natural language. They are extremely easy to use, and in today's growing digital world, their use is expected to continue to grow. It is no exaggeration to say that everything from home speakers to pocket-type smartphones has become established in everyday life. The purpose of this study is to understand the increasing use of voice assistants in our daily lives. How to cite this article: Agarwal A, Mishra A, Tiwari S et al. Virtual Voice Assistant using Python. J Adv Res Info Tech Sys Mgmt 2022; 6(1): 25-29.